IMPROVING THE RELIABILITY OF TRANSFORMERS IN DISTRIBUTION NETWORKS - Murtazoyev Firdavs Feruzovich (Web of Journals Publishing, 2024)
Various methods for improving the reliability of transformers in distribution networks are considered, and the reasons for their reduced service life are analyzed.
Keywords: Distribution transformers, regeneration, diagnostics, monitoring, adsorbent, insulation wear, load flow.